Studi Perbandingan Kelas Kemampuan Kelompok Wanita Tani Kecamatan Koto Tangah Kota Padang Sumatera Barat - Devi Analia; Meira Sutri; Rudi Febriamansyah (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
This research aims to assess and analyze the comparison of the ability classes of groups of women farmers who are standing with encouragement and groups of women farmers who are standing independently in Parupuk Tabing Village, Koto Tangah District, Padang City. The data were analyzed descriptively, guided by the guidebook for assessing farmer groups' ability classes issued by the Agricultural Extension and Human Resources Development Agency Number: 168/Per/SM.170/J/11/11 Center for Agricultural Extension in 2023. The research results showed that The group of women farmers who stood up with encouragement from the government got a score of 331, while the group of women farmers who stood up independently got a score of 229. From this score, the assessment of the ability class of the farmer group, the group of women farmers who stood up with support from the government scored higher than the group of women farmers independently. This group turned out to be in the advanced or quite good category. However, there are still groups that do not have aspects of group ability, such as the ability to plan, these two groups both do not have the ability to plan.